Peer-assessment in projects : an analysis of qualitative feedback - Hattum-Janssen, Natascha van (2011)
Learning through projects can increase involvement of students in the assessment process, especially in the assessment of the development of transferable competencies. The responsibilities in the assessment process can be shifted from the teacher to the students, so that the students become engaged in a process that helps them to analyse and understand the way they perform in a group project and how this performance contributes to the final result of the project. In the context of a 15 ECTS course at the second and final year of Informatics Engineering Master´s Degree programme, students had to carry out a project in the first semester. The performance of each student was evaluated through peer assessment in subgroups. This paper describes the peer assessment schedule that was used, analyses the qualitative comments that were given and reflects on the impact of the peer assessment scheme on the results of the project.